Development of stimuli-responsive flexible micropillar composites via magneto-induced injection molding and characterization of magnetic particle alignment - Jin Wook Park; Jong Hyun Kim; Kwang Seok Lee; Sang Min Park; Da Seul Shin (Polymer Testing, 2024)
Magnetic soft composites have emerged as a promising soft actuator with a high degree of precision in the magnetic field stimuli system. But, their mass manufacturing strategies have yet to be developed, and most studies focus on small-scale near-net shaping production. Here, we first apply injection molding (which only takes a few seconds to shape) to fabricate the stimuli-responsive flexible micropillar composites with magnetic particle alignment design using an external magnetic field. The arrays exhibit magnetically anisotropic particle alignment up to 82.57 % along the longitudinal direction, showing a magnetic bending actuation response. We achieve a structural novelty of the magnetic micropillar with a high aspect ratio of up to 10 and pattern sizes of 50 μm via sacrificial LIGA insert mold and magneto-induced injection molding. For advanced mass production, the permanent metal mold is also applied to develop the micropillar composites based on the mechanical demolding approach; successful manufacturing is achieved by fabricating defect-free micropillar with 200 μm cylindrical pattern size and aspect ratio of 6. Further, the effect of powder volume fraction on the magneto-rheological behavior and corresponding magnetic performance is characterized in the injection molding process. The magnetic particle alignment trend is confirmed by the torque balance and the criteria of critical solids loading. Finally, we establish an injection molding process for magnetic soft composites, and verify the optimal powder fraction for the particle alignment.